Opinion on Performing Pathology Peer-Review During the Global Pandemic: Challenges and Opportunities. (December 2020) - Hukkanen, Renee R.; Irizarry, Armando; Fikes, James D.; Schafer, Kenneth A.; Boyle, Molly H.
The coronavirus disease 2019 pandemic has affected business on numerous fronts in unprecedented and abrupt ways. From site closures and local "stay-at-home orders" to travel advisories and restrictions, the day-to-day practice of toxicologic pathology has been impacted dramatically and rapidly. A critical function of Toxicologic Pathologists is performing pathology peer review for nonclinical studies. Traditionally, corroborating the findings of histological assessment could be achieved through shipment of histopathological slides to the peer review pathologist, or by the peer review pathologist traveling to the location of the slides (eg, the test facility). Since early 2020, many pathologists have been unable to perform the latter due to local, regional, national, test facility, company, and/or personal restrictions. The disruption for some has been minimal, while others are working from home for the first time. We recommend that contingency plans for all peer review procedures and personnel should be in-place to accommodate sudden and unexpected workflow transitions. Now, more than ever, approaching peer reviews with enhanced adaptability will help ensure success.